THE INFLUENCE OF TRUST, EASE OF USE, AND RISK PERCEPTION ON PURCHASE INTENTION AT TOKOPEDIA - Tarizqa Putri Aurelia; KS Widiantari (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
The purpose of this study is to examine the relationship between trust, ease of use, and risk perception on purchase intention at Tokopedia. This study employs quantitative methods, with purposive sampling as the sampling method. The participants in this study are Tokopedia users who reside in Denpasar City. The total number of samples used in the research was 85. According to this study's findings, trust has a positive and significant effect on purchase intention, as does ease of use, while risk perception has a negative and significant effect on purchase intention.